Are Infrared and Microwave Drying Suitable Alternatives for Moisture Determination of Meat Products?. Issue 4 (21st January 2016) - Marques, Ítalo Engers; Lucion, Fernanda Bortoluzzi; Bizzi, Cezar Augusto; Cichoski, Alexandre José; Wagner, Roger; de Menezes, Cristiano Ragagnin; Barin, Juliano Smanioto
Abstract: The analytical methods used for routine moisture determination are based on a loss on drying (LOD) approach performed by conventional heating in ovens, but infrared loss on drying (IRLOD) and microwave‐assisted loss on drying (MALOD) drying methods have been used to reduce the analysis time. MALOD speeds up water removal from meat products 64 times in comparison to LOD and provided similar results (agreement between 98 and 101%), but with lower energy consumption (<1 and 31 kWh for MALOD and LOD, respectively) and higher sample throughput (60 samples/h). Infrared thermographies showed temperature of 107.8C in MALOD, which is similar to those used in conventional ovens (105 and 120C). For IRLOD the results were generally lower and its use for meat products should be carefully considered. A fast and accurate analysis of moisture in meat products could be achieved using microwaves, saving time and energy expenditure in agreement to green analytical chemistry. Practical Applications: Moisture is a routine analysis performed in every industrial and academic laboratory interested on the study of meat and its products. However, different analytical methods are used for this purpose, and often different results are obtained. Therefore, in this study the performance of three methods based on loss on drying (using conventional, infrared or microwave heating) were evaluated. The results showed lower moisture content by the use of infrared balances for all samples and its use should be carefully evaluated to avoid systematic errors. Contrarily, the results obtained by the use of microwaves were comparable with those of conventional heating, but several advantages were found. The energy consumption was reduced at least 31 times and 15 samples could be processed simultaneously in only 15 min opening the possibility of use of this method to improve routine analysis or as an analytical technique for processing control.